2021
DOI: 10.3389/fmicb.2021.764733
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Inhibitor of Bacterial Polyphosphate Homeostasis Attenuates Virulence Factors and Helps Reveal Novel Physiology of Klebsiella pneumoniae and Acinetobacter baumannii

Abstract: Acinetobacter baumannii and Klebsiella pneumoniae currently rank amongst the most antibiotic-resistant pathogens, responsible for millions of infections each year. In the wake of this crisis, anti-virulence therapeutics targeting bacterial polyphosphate (polyP) homeostasis have been lauded as an attractive alternative to traditional antibiotics. In this work, we show that the small molecule gallein, a known G-protein βγ subunit modulator, also recently proven to have dual-specificity polyphosphate kinase (PPK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…Gallein also synergized with the antibiotics tetracycline and ciprofloxacin to improve C. elegans survival following P. aeruginosa infection [ 57 , 82 ]. In a follow-up study, we also demonstrated that gallein inhibits A. baumannii and K. pneumoniae PPK2s in vitro [ 42 ] ( Table 2 ).…”
Section: Therapeutic Potential: Ppk2 Inhibitorsmentioning
confidence: 92%
See 4 more Smart Citations
“…Gallein also synergized with the antibiotics tetracycline and ciprofloxacin to improve C. elegans survival following P. aeruginosa infection [ 57 , 82 ]. In a follow-up study, we also demonstrated that gallein inhibits A. baumannii and K. pneumoniae PPK2s in vitro [ 42 ] ( Table 2 ).…”
Section: Therapeutic Potential: Ppk2 Inhibitorsmentioning
confidence: 92%
“…ppk2 genes have been identified in many species of both Gram-positive and Gram-negative bacteria [ 35 ], with several species encoding multiple distinct isoforms [ 35 , 39 , 40 ] ( Table 1 ). For example, P. aeruginosa possesses three distinct PPK2s [ 39 ], whereas other pathogenic bacteria such as Mycobacterium tuberculosis [ 41 ] or Klebsiella pneumoniae [ 42 ] possess only a single PPK2 isoform. In a more extreme instance, the environmental bacterium Ralstonia eutropha contains five distinct PPK2 enzymes, further illustrating the genetic abundance and variability among PPK2s [ 40 ] ( Table 1 ).…”
Section: Ppk2: a New Class Of Polyp-metabolizing Enzymementioning
confidence: 99%
See 3 more Smart Citations